Use of classification and regression tree (cart) for chronic periodontitis classification in dental hospital of Hang Tuah University Surabaya - Aulia Dwi Maharani (Universitas Wijaya Kusuma Surabaya, 2015)
Classification and Regression Tree (CART) is now commonly used as one of nonparametricclassification methods. The advantage of this method is it can effectively used on data whichhave many independent variables. It is also easy to be interoperated.The aim of this research is to classify Chronic Perodontitis in Dental Hospital of Hang TuahUniversity Surabaya using CART. The Chronic Periodontitis divided into 3 categories: mild,moderate, and heavy. Based on the analysis result, 2 factors can affected the mild type ofchronic periodontitis , 6 factors affected moderate type of chronic periodontitis and 8 factorsaffected the heavy type of chronic periodontitis.The criteria used to count the accuracy of the CART classification is 1-APER. The 1-APERscore shows a very good result which is 92,5% for data learning and 90% for data testing.